Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10:
ISBN 13:

Chapter 9 - Basic Algebra - 9.7 Solving Equations with Several Steps - 9.7 Exercises - Page 678: 67

Answer

t =-3

Work Step by Step

-2t - 10 = 3t + 5 One way to get the variable term by itself on one side is to add 2t from both sides. -2t - 10 + 2t = 3t + 5 +2t -10 = 5t +5 Next, add -5 to both sides -10 -5= 5t +5 -5 -15 = 5t Finally, divide both sides by 5 $\frac{-15}{5}$ = $\frac{5t}{5}$ -3 = t The solution is -3. Check. Go back to the original equation -2t - 10 = 3t + 5 Replace t with -3 -2 * -3 -10 = 3* -3 +5 6 - 10 = -9 +5 -4 = -4 True, so -3 is the correct solution
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.